TEOLOGI BURUH: Agama dan Sikap Pasrah Perempuan Buruh Sanggan Batik - Rita Rahmawati; M. Muslih Husein; Asmuni Hayat (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2014)
This qualitative descriptive research aimed to describe in detail the meaning of the values of religion and expression of women's resignation batik workers in the struggle of the production process, and the factors that influence it. Research was taken place in Pekalongan city and data obtained through observation, interviews, and literary studies. The results showed that deep belief in God is the foundation of understanding of the value of religion in the world of work as well when they interact with the skipper and other workers. The expression of resignation is seen almost in all stages from raw material procurement, production to marketing. Surrender women sanggan also evident in labor relations and outside the employment relationship, which is due to the fact that the religious elite is skipper and social conditions of patriarchal religious culture.